Efektivitas Media Pembelajaran NEARPOD terhadap Kemampuan Berpikir Logis Peserta Didik SMA - Zainab, Siti; Rafiq Badjeber; Riska Elfira (Media Pendidikan Matematika, 2025)
This study aims to determine the effectiveness of the Nearpod learning media on students’ logical thinking skills in the quadratic equation topic at MAN 2 Kota Palu. The research employed a quantitative approach with a pretest-posttest control group design. The sample consisted of two classes: an experimental class that received instruction using Nearpod and a control class that received conventional teaching. The research instrument was a logical thinking test administered before and after the treatment. The normality test indicated that the data were not normally distributed; therefore, the Mann–Whitney U test was used for data analysis. The results showed that the Asymp. Sig. (2-tailed) value of the posttest was 0.103 (> 0.05), indicating no statistically significant difference between the two groups. However, the experimental class obtained a higher Mean Rank than the control class, suggesting a descriptive improvement in students’ logical thinking skills. These findings imply that Nearpod provides a positive influence, even though the statistical effect is not significant. This study highlights that digital learning media such as Nearpod have the potential to enhance student engagement and higher-order thinking skills when implemented consistently and supported by adequate technological infrastructure